DINAMIKA SOSIAL DALAM TRADISI MAHAR ADAT ALAS ACEH TENGGARA PERSPEKTIF IMAM SYAFI’I - Wahyu Ansahrizal; Nurliza, Fitri (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
The tradition of Mahar in marriage is one of the traditions found in various societies and cultures in Indonesia, including the Alas Custom of Southeast Aceh. This research aims to analyze and know qualitatively about the Social Dynamics of the Mahar Tradition of Southeast Aceh Alas Custom from Imam Syafi'i Perspective. This research uses descriptive qualitative method. The research data comes from supporting literature such as books, journals, and other relevant sources. The results of this study indicate that the tradition in determining the amount of Alas customary dowry in Southeast Aceh is carried out by means of Mekhdat (Customary Deliberation), the tradition is acceptable to the community and does not conflict with the teachings of Islam. Imam Syafi'i gives a view of the dowry as a mandatory gift of the prospective husband either in the form of objects or services. The size of the dowry is not an absolute requirement, so as not to complicate the marriage so that there are no bad implications.